INVESTIGATING THE IMPACT OF SYSTEMIC ALENDRONATE ON PERIODONTAL PARAMETERS IN OSTEOPOROSIS AND PERIODONTITIS PATIENTS. AN INTERVENTIONAL AND PROSPECTIVE STUDY - Georgeta-Maria Laza; Maria-Alexandra Martu; Irina-Georgeta Sufaru; Silvia Martu; Liliana Pasarin; Ioana Martu (Romanian Society of Oral Rehabilitation, 2024)
Patients with osteoporosis exhibit a nearly twofold higher diagnosis rate of periodontitis compared to the general population, indicating osteoporosis is a potentially significant risk factor for periodontitis development. This study explored changes in periodontal and radiological parameters after systemic alendronate use in osteoporotic patients with periodontal disease. Sixty-four post-menopausal adults diagnosed with osteoporosis and periodontal disease were divided into two groups: Group A, without bisphosphonate therapy, and Group B, receiving alendronate (70mg/week) for 12 months. Both groups underwent non-surgical periodontal treatment. Parameters including plaque index (PI), bleeding on probing (BOP), probing depth (PD), clinical attachment loss (CAL), and radiographic infrabony defect depth (IBD) were evaluated at baseline and after 12 months. Oral administration of alendronate at 70 mg/week for 12 months was found to be safe and effective in enhancing the outcomes of non-surgical periodontal therapy both clinically and radiologically. This suggests alendronate could be a valuable adjunctive treatment for managing periodontal disease in osteoporotic patients.